Ferroptosis spreads to neighboring cells via plasma membrane contacts - Bernhard F. Roeck; Sara Lotfipour Nasudivar; Michael R. H. Vorndran; Lena Schueller; F. Isil Yapici; Matthias Rübsam; Silvia von Karstedt; Carien M. Niessen; Ana J. Garcia-Saez (Nature Communications)
Abstract Ferroptosis is a lytic, iron-dependent form of regulated cell death characterized by excessive lipid peroxidation and associated with necrosis spread in diseased tissues through unknown mechanisms. Using a novel optogenetic system for light-driven ferroptosis induction via degradation of the anti-ferroptotic protein GPX4, we show that lipid peroxidation and ferroptotic death can spread to neighboring cells through their closely adjacent plasma membranes. Ferroptosis propagation is dependent on cell distance and completely abolished by disruption of α-catenin-dependent intercellular contacts or by chelation of extracellular iron. Remarkably, bridging cells with a lipid bilayer or increasing contacts between neighboring cells enhances ferroptosis spread. Reconstitution of iron-dependent spread of lipid peroxidation between pure lipid, contacting liposomes provides evidence for the physicochemical mechanism involved. Our findings support a model in which iron-dependent lipid peroxidation propagates across proximal plasma membranes of neighboring cells, thereby promoting the transmission of ferroptotic cell death with consequences for pathological tissue necrosis spread.